E-Tailing in India: Present and Future Growth - Prasad, S. K.; Rajesh, P. S. (Indian Journal of Computer Science, 2019)
Internet is a potent medium that can serve as a unique platform for the growth of retail brands in India. Indian e-retail market is witnessing a revolution. Brand awareness has been created in Tier II and III cities but the required products or services are not available. To overcome this problem, e-retailers need to penetrate into Tier II and III Indian cities more as compared with developed countries. There are certain factors in the business environment of India that can prove to be useful for online traders like changing consumer purchasing habits, internet speed, updated technology etc. So, these e-retailing companies should frame their strategies to capture more market share. This paper highlights the essentials of e-tailing in India, factors of growth, and barriers to growth of e-tailing in India.